Merger decisions, accounting information and performance stability inside and outside of economic crisis periods: evidence from Greece - Pazarskis, Michail; Giovanis, Nikolaos; Koutoupis, Andreas; Chasiotou, Aikaterini (Journal of Business Economics and Management, 2022)
This study examines the merger decisions from a sample of Greek listed companies in the economic crisis period and shortly after its end, by employing various quantitative and qualitative variables of mergers that signalize different levels of risk. The results revealed that the performance subsequent of mergers is not significantly different for the merged companies. But in comparison to control sample of companies without mergers for the examined period, the results reveal that merger transactions signalize a more stable profitability and better performance for the companies with mergers. Furthermore, merger events signalize different performance levels during and after the crisis: mergers that took place when there was no economic crisis are far more profitable and lead to better performance from mergers during the period of economic crisis. Last, regarding the industry relatedness of the merged firms, the industry type and the merger combination of merged companies, there is not any impact from them on the post-merger performance in the examined accounting measures. The study proposes for companies that during crisis periods maybe merger be the only way to survive and provide a stable profitability and accounting performance for shareholders.